Parametric study of catalytic hydropyrolysis of rice husk over a hierarchical micro-mesoporous composite catalyst for production of light alkanes, alkenes, and liquid aromatic hydrocarbons. (15th February 2022) - Li, Zhaoying; Zhong, Zhaoping; Yang, Qirong; Ben, Haoxi; Seufitelli, Gabriel V.S.; Resende, Fernando L.P.
Highlights: The CHP of lignocellulosic biomass was carried out over a hierarchical catalyst. The products of CFP and CHP of rice husk are compared. CHP of rice husk (RH) over hierarchical catalyst led to a high hydrocarbons content. The optimum conditions for the CHP of RH were 400 °C and 35 bar. Abstract: In this study, we compare the products of catalytic fast pyrolysis (CFP) and catalytic hydropyrolysis (CHP) of rice husk over an HZSM-5-based hierarchical catalyst. The results suggest that the addition of hydrogen inhibits polycondensation reactions, leading to a reduction of 2.3 wt% in coke yield at 400 °C and 35 bar. The presence of hydrogen increases the relative content of hydrocarbons in both liquid and gas products, with a more significant increase in CH4 and C2 –C3 yield in the gas, suggesting that hydrodeoxygenation, decarbonylation, and decarboxylation reactions are promoted. Alkali-treatment of the HZSM-5 improves the catalytic activity and coking resistance of the catalyst. The addition of an extra external MCM-41 layer to the alkali-treated HZSM-5 further improves the catalytic activity, resulting in a relative hydrocarbon content of 48.9%, which is higher than that obtained with the alkali-treated HZSM-5 and pristine HZSM-5. We also report the effect of pressure on the products. As the pressure increases from 1 to 35 bar, the relative content of hydrocarbons increases from 39.9 to 48.9%, while the coke yield decreases from 3.4 to 1.9 wt%, and CH4 and C2 –C3 yields decrease from 10.3 wt% and 5.1 wt% to 14.2 wt% and 6.7 wt%, respectively. As the temperature increases from 300 to 400 °C, the relative content of hydrocarbons increases from 38.2% to 48.9%. Both CH4 and C2 –C3 yields reach the highest values of 14.2 wt% and 6.7 wt% at 400 °C and 35 bar.